PENGARUH OPINI AUDIT TERHADAP REAKSI PASAR SAHAM DAN NILAI PERUSAHAAN - Catherine; Rina Tjandrakirana (PT Wahana Global Education, 2025)
This study examines the impact of audit opinions on firm value and market reactions using the Systematic Literature Review (SLR) method. Audit opinions serve as critical signals to investors, reflecting a company's financial transparency, credibility, and stability. An unqualified audit opinion generally reinforces investor confidence, leading to higher firm value and positive market reactions. In contrast, modified audit opinions, including qualified, adverse, and going concern opinions, raise concerns about financial risks, potentially leading to declining firm value, increased stock price volatility, and heightened investment uncertainty. The findings indicate that audit opinions significantly shape investor perceptions and decision-making. Companies that consistently receive unqualified audit opinions tend to attract stronger investor interest, enjoy greater market stability, and experience lower stock price fluctuations. Conversely, companies with modified audit opinions face higher investment risks, diminished investor confidence, and potential stock price declines. This research highlights the crucial role of audit quality and transparency in financial reporting. Obtaining a unqualified audit opinion is essential for maintaining market trust, enhancing firm value, and ensuring financial stability. These insights provide valuable implications for investors, regulators, and corporate management, emphasizing the importance of high-quality financial audits in fostering a stable and trustworthy market environment.